Magnetic and transport properties controlled by structural disorder in La0.7Ca0.3MnO3 films - Prokhorov, V.G.; Komashko, V.A.; Kaminsky, G.G.; Svetchnikov, V.L.; Lee, Y.P.; Park, S.Y. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
The magnetic properties of an amorphous, a partially-disordered, and a lattice-strained crystallineLa0.7 Ca0.3 MnO3 film are investigated. It is shown that the amorphous film exhibits Curie-Weiss-type paramagnetism with the effective magnetic moment of 4.2 mB/Mn ion and a smallferromagnetic contribution governed by the formation of a quasi-two-dimensional crystalline interfacialinclusions. The crystalline film with nanocrystalline randomly-oriented inclusions demonstrates a superposition of ferromagnetic (in the crystalline matrix) and superparamagnetic (in the inclusions) nature. The fitted average size of the superparamagnetic particles in the case of a Langevin function is coincident with that of the nanocrystalline clusters reveated in high-resolution electron-microscopy images. An increase in the applied magnetic field leads to a reduction in the average magnetic moment of superparamagnetic particles, which is due to an enhancement of the ferromagnetic coupling between the individual randomly-oriented crystallites. The completely crystalline film undergoes only a ferromagnetic transition with a saturation magnetization at 5 K of 2.73 mB/Mn ion.